Dampak Stigma Masyarakat Terhadap Keterbatasan Ruang Sosial Bagi Para Penyintas Covid-19 di Kota Cirebon - Khusnul Khotima (Empower : Jurnal Pengembangan Masyarakat Islam, 2021)
Covid-19 began to enter Indonesia in 2020. The virus is increasingly spreading in various regions in Indonesia, including the city of Cirebon. Many people have been exposed to the virus, so there are also many Covid-19 survivors in the Cirebon area. For survivors, acceptance from the community is critical to the recovery process. However, due to the spread of hoax news about Covid-19, most people have a negative stigma towards Covid-19 survivors, so this has limited social space for survivors in the community. This study uses a descriptive qualitative method, where interviews with survivors are one of the techniques of data collection. This research shows that the stigma of society towards Covid-19 and the survivors creates various negative perceptions, so that the survivors who should get more sympathy or care, are the opposite. Many survivors are ostracized, ridiculed, shunned, some even feel they have lost their self-esteem.